Fiqh Al-Lughah Dan Pengaruhnya Terhadap Perkembangan Ilmu Nahwu - Ifrohatul Hamidah; Ainur Rofiq Sofa (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Fiqh al-Lughah is a discipline that examines the philosophical and historical aspects of the Arabic language, including the factors influencing its development. One of the most rapidly growing branches of Arabic language studies is Nahwu (grammar), which plays a crucial role in understanding linguistic structures and rules. This study aims to analyze the relationship between Fiqh al-Lughah and the development of Nahwu and how a deeper understanding of Fiqh al-Lughah contributes to the analysis and application of Nahwu rules. This research employs a qualitative method with a descriptive-analytical approach based on classical and modern literature reviews. The findings indicate that Fiqh al-Lughah significantly influences the formation of Nahwu theories, particularly in the historical development of grammatical rules, word classification, and syntactic concepts in Arabic.